PELATIHAN UMKM PEMBUATAN SABUN CUCI PIRING DI DESA BESADI KEC KUALA KAB LANGKAT - Rifanny Balqis; M Laksamana Ghafur; Syahrul Ramadhan Dlt; Ucok Kurnia Meilala; Putri Silaen; Sapna Tanjung; Dinda Monica Sari; Amanda Pratiwi; Febrya Ardiansyah; Dheaameliananda Lubis (CV. KAMPUS AKADEMIK PUBLISING, 2025)
The MSME dish soap production training in Besadi Village, Kuala District, Langkat Regency, was conducted as part of a community empowerment effort to improve skills, independence, and the local economy. This activity was motivated by the community's need to utilize local potential while simultaneously opening up new business opportunities based on household skills. Dish soap production was chosen due to its high economic value, stable market demand, and readily available and affordable raw materials. Through this training, participants were provided with a theoretical understanding of the ingredients, measurements, and simple chemical processes involved, as well as hands-on practice to produce a high-quality, environmentally friendly, and market-competitive product. This training not only improved technical skills but also fostered an entrepreneurial spirit, including business planning, packaging, marketing strategies, and simple financial management. The results of the training demonstrated high enthusiasm from the community, particularly housewives and youth, who recognized new business opportunities based on dish soap production. Therefore, this training has the potential to be the first step in promoting economic independence in the Besadi Village community and strengthening the MSME sector in rural areas.